Managing online crisis-communication response in a South African bank - Rachel Barker (Communicare)
Deregulation and rapid growth in technology removed entry barriers in the online environment, thereby forcing financial institutions to transform and at the same time to conquer consumer’s fear and the perceived risk of fraudulent online transactions. Given the nature of operations and services in the banking sector, it is relatively amenable to innovative technologies, especially online banking transactions. Various studies have been conducted on the adoption of self-service technology, specifically the continued use of this technology, perceived risk in online transactions, and also purchase intention. However, very little research has examined the management of online crisis-communication response messages in the online-security sphere. The knowledge management paradigm constitutes a way in which the acquisition, transfer and assimilation of information can be effectively used to manage and control messages in an online crisiscommunication response situation, in particular through maximising consumers’ motivation and capability to act in response to perceived online-transaction risks. Hence, it provides a means of reliance upon self-motivation and empowerment of individuals to ensure output control and the safety of online banking transactions. The aim of this paper is to present a comparative analysis of the knowledge management of online crisis-communication response in respect of fraudulent banking transactions in one of the top ten banks in South Africa during two specified time periods. The paper first presents a synopsis of the theoretical underpinning based on an extensive literature review. The latter focuses on web communication, online crisis-communication response, fraudulent banking transactions and knowledge management. The methodology, data analysis and results are subsequently presented. Finally, a discussion of the main results based on the knowledge-management typologies proposed to manage and control messages in online crisis-communication response is presented